BIOCHEMICAL BASIS AND EMERGING MOLECULAR TARGETS TO TREAT DIABETIC RETINOPATHY - SUCHITRA, KUMARI; TARUN K, PANDA (International Journal of Clinical and Biomedical Research, 2016)
Diabetes being considered as an epidemic, long term untreated complicated diabetes resulting in retinopathy will be a leading cause of blindness worldwide. Many cross-sectional studies reported a strong relationship between chronic hyperglycaemia and development, progression of retinopathy, however the underlying mechanism that cause retinal microvascular damage following prolonged hyperglycaemia, yet to be revealed. Continued research worldwide focuses on understanding the molecular basis with the ultimate goal to prevent diabetic retinopathy by developing newer therapeutic targets. This article reviews multiple biochemical pathways that are implicated in diabetic retinopathy. Recent advancement in the molecular basis of the disease as well as clinical trials undertaken to target these molecules in order to block the signalling cascade prevailing in diabetic retinopathy is also discussed. This review highlights the recent therapeutic targets to prevent the onset as well as the progress of retinopathy in diabetes.